Peran Literasi Keuangan Syariah sebagai Katalisator Pertumbuhan Industri Keuangan Syariah - Ria Nelta Febriyanti (Al-Iqtishad: Jurnal Ekonomi Syariah, 2024)
This study aims to examine the role of sharia financial literacy as a catalyst for the growth of the sharia financial industry in Indonesia. The data used in this research comes from data from Otoritas Jasa Keuangan (OJK) and Bank Indonesia from 2015 to 2023. The results of this study show that there is a positive correlation between increasing sharia financial literacy and the growth of the sharia financial industry in Indonesia. In addition to increasing public understanding of sharia financial products and services, increasing sharia financial literacy is also expected to increase the utilization and use of sharia financial products and services due to increasing public trust in sharia financial products and services. The role of good financial literacy can also increase innovation in sharia financial products and services, strengthening industrial competitiveness. Therefore, it is necessary to carry out various further educational and outreach efforts to increase sharia financial literacy in the community. Key words: Sharia Financial Literacy, Industry Growth, Sharia Finance.